Ephemeroptera, Plecoptera and Trichoptera (Insecta) Abundance, Diversity and Role in Leaf Litter Breakdown in Tropical Headwater River - Suhaila Ab Hamid,; Che Salmah Md Rawi, (Tropical Life Sciences Research, 2017)
Leaf litter decomposition in a tropical stream was examined in two types of leaf packs; single species leaf packs of Pometia pinnata and two species leaf packs of equal combination of Pometia pinnata and Dolichandrone spathacea leaves. Both leaf packs were immersed in a river and weekly examined for remains of decomposed leaves and presence of EPT. In the control leaf packs, leaves in the two species leaf packs treatments decomposed within 35 days, faster than in single species leaf packs which decomposed after 42 days. In the presence of EPT, the leaf breakdown took 28 days in two species and 35 days for single species leaf packs. Higher abundance of EPT was observed in single species leaf packs but its diversity was higher in two species leaf packs. Litter breakdown in the stream was faster in the presence of EPT and softer leaves of D.spathacea with higher nitrogen content underwent faster decomposition and sustained higher numbers of EPT. Penguraian sampah daun di dalam aliran tropika diperiksa dalam dua jenis pek daun; Pek daun spesis tunggal Pometia pinnata dan dua pek daun spesis yang sama dengan kombinasi Pometia pinnata dan daun Dolichandrone spathacea. Kedua-dua pek daun telah direndam di dalam sungai dan diperiksa setiap minggu untuk sisa-sisa daun terurai dan kehadiran EPT. Dalam pek daun kawalan, daun dalam dua pek spesies rawatan daun terurai dalam masa 35 hari, lebih cepat daripada satu pek daun spesies tunggal yang terurai selepas 42 hari. Pecahan daun mengambil masa 28 hari dalam dua spesies dan 35 hari untuk pek daun spesies tunggal dengan kehadiran EPT. Kelimpahan EPT yang lebih tinggi diperhatikan dalam pek daun spesis tunggal tetapi kepelbagaiannya lebih tinggi dalam dua pek daun spesis. Kerosakan sampah di aliran lebih cepat dengan kehadiran EPT dan daun lembut D.spathacea dengan kandungan nitrogen yang lebih tinggi mengalami penguraian lebih cepat dan mempertahankan jumlah EPT yang lebih tinggi.